1988
DOI: 10.1071/ar9880907
|View full text |Cite
|
Sign up to set email alerts
|

Clinical footscald and footrot in a New Zealand Romney flock: phenotypic and genetic parameters

Abstract: Phenotypic and genetic parameters for clinical footscald and footrot were investigated in a pedigree flock of New Zealand Romney sheep inspected during outbreaks over six years. At inspections, each sheep's overall status with regard to footscald and footrot was summarized on a combined severity scale (Rating). Sheep were also categorized in terms of two binomial variables specifying the presence or absence of footscald or footrot (FI) and the presence or absence of footrot only (FR). A trinomial variable spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 16 publications
5
20
1
Order By: Relevance
“…The resulting estimate of 0.35 does not support the suggestion that the footrot results may be an artefact the data structure. The zero heritability contrasts with results for footrot presented by Skerman et al (1988) and Raadsma et al (1994) who found low to medium heritabilities in lambs, although the lambs in these two studies were older, i.e. 8 to 10 months at the start of trial, than in (2) 2006 (1) 2006 (2) 2005 ( the current study where they were an average of 5 months at time of scoring.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…The resulting estimate of 0.35 does not support the suggestion that the footrot results may be an artefact the data structure. The zero heritability contrasts with results for footrot presented by Skerman et al (1988) and Raadsma et al (1994) who found low to medium heritabilities in lambs, although the lambs in these two studies were older, i.e. 8 to 10 months at the start of trial, than in (2) 2006 (1) 2006 (2) 2005 ( the current study where they were an average of 5 months at time of scoring.…”
Section: Discussioncontrasting
confidence: 95%
“…Although differences in heritability estimates for lesion scores were found across the breeds, these estimates do not differ greatly from each other or from previously published values for resistance to footrot. In SBF, the heritability for foot lesions was estimated to be 0.19 and in mules 0.12, this is comparable to 0.16 and 0.31 estimated by Raadsma et al (1994) in Merino lambs and 0.28 for Romney (Skerman et al, 1988, trait defined as footrot or scald), especially when taking into account the effect of prevalence. The respective figures for severe lesions are SBF 0.26, mules 0.19, Merino (1), 0.21, Merino (2) 0.16 and Romney 0.17 (footrot only).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Genetic variation in resistance to footrot has been demonstrated (Skerman et al, 1988;Raadsma et al, 1994;Conington et al, 2007), with the heritability depending on the definition of footrot (number of classes, observed or underlying scale) and reaching values up to 0.3. While Raadsma et al (1994) showed an increased risk of footrot with heavier live weights, they did not estimate the effect of footrot on live weight gain.…”
Section: Introductionmentioning
confidence: 99%